The Biphasic Effect of Vitamin D on the Musculoskeletal and Cardiovascular System - Armin Zittermann (International Journal of Endocrinology)
This narrative review summarizes beneficial and harmful vitamin D effects on the musculoskeletal and cardiovascular system. Special attention is paid to the dose-response relationship of vitamin D with clinical outcomes. In infants and adults, the risk of musculoskeletal diseases is highest at circulating 25-hydroxyvitamin D (25OHD) concentrations below 25 nmol/L and is low if 40–60 nmol/L are achieved. However, evidence is also accumulating that in elderly people the risk of falls and fractures increases again at circulating 25OHD levels > 100 nmol/L. Cohort studies report a progressive increase in cardiovascular disease (CVD) events at 25OHD levels < 50 nmol/L. Nevertheless, meta-analyses of randomized controlled trials suggest only small beneficial effects of vitamin D supplements on surrogate parameters of CVD risk and no reduction in CVD events. Evidence is accumulating for adverse vitamin D effects on CVD outcomes at 25OHD levels > 100 nmol/L, but the threshold may be influenced by the level of physical activity. In conclusion, dose-response relationships indicate deleterious effects on the musculoskeletal system and probably on the cardiovascular system at circulating 25OHD levels < 40–60 nmol/L and >100 nmol/L. Future studies should focus on populations with 25OHD levels < 40 nmol/L and should avoid vitamin D doses achieving 25OHD levels > 100 nmol/L.